The impact of novel therapeutic agents before and after frontline autologous stem cell transplantation in patients with multiple myeloma - Min, Chang-Ki; Lee, Sung-Eun; Yahng, Seung-Ah; Cho, Byung-Sik; Eom, Ki-Seong; Kim, Yoo-Jin; Kim, Hee-Je; Lee, Seok; Cho, Seok-Goo; Kim, Dong-Wook; Lee, Jong-Wook; Min, Woo-Sung; et al. (Blood research, 2013)
Novel agents (NAs) such as thalidomide and bortezomib have been administered in combination with autologous stem-cell transplantation (ASCT) to effectively treat multiple myeloma (MM). However, whether NAs perform better as induction treatments prior to transplantation, or as post-transplant maintenance therapies remains unclear. We retrospectively analyzed 106 consecutive patients with MM who underwent ASCT within 1 year of diagnosis as first-line therapy. Eighty-seven (82.1%) patients received NAs before ASCT, whereas 68 (64.2%) received NAs after ASCT. NAs were administered to each patient as follows: before ASCT alone (N=29, 27.4%), after ASCT alone (N=10, 9.4%) or both before and after ASCT (N=58, 54.7%). High-quality rates before and after ASCT were significantly higher for patients who received NAs as induction treatment compared to those who did not receive pre-transplant NAs. At a median follow-up of 37.9 months, the 3-year progression-free survival (PFS) and overall survival (OS) rates were 42.8% and 70.2%, respectively. The PFS and OS were significantly higher in patients with NAs as post-transplant maintenance treatment (P=0.03 and P=0.04, respectively), but not in those with NAs as pre-transplant induction treatment. The PFS of patients with NAs before and after ASCT was higher than that of the patients with NAs as induction therapy alone (P=0.05). Age, serum β2-microglobulin level, complete response after ASCT, and NA use post-ASCT independently predicted survival outcomes. These findings suggest that integration of NAs post-ASCT could benefit patients with MM undergoing ASCT. Induction therapy using NAs also improves high-quality response rates before and after ASCT.